Population and ecological study of agarwood producing tree (Gyrinops versteegii) in Manggarai District, Flores Island, Indonesia - RIDESTI RINDYASTUTI; TITUT YULISTYARINI; AGUNG SRI DARMAYANTI (Biodiversitas Journal of Biological Diversity, 2019)
Abstract. Rindyastuti R, Yulistyarini T, Darmayanti AS. 2019. Population and ecological study of agarwood producing tree (Gyrinops versteegii) in Manggarai District, Flores Island, Indonesia. Biodiversitas 20: 1180-1191. Gyrinops versteegii (Gilg) Domke is one of very important tree species listed in Appendix II CITES because of its economical value as a source of agarwood. Since this commodity has been harvested in a significant volume, the natural population of G. versteegii is continuously decreasing in size. A remnant forest of Pongkor is one of fragmented habitat of G. versteegii in the rest of other land use for rice farming in Flores Island. The purpose of this study were to investigate the population structure and importance value rank of G. versteegii among plant species in Pongkor Community Forest. A semi-purposive random sampling were used in this study to investigate the population of G. versteegii in Pongkor, Manggarai District. The result showed that G. versteegii in Pongkor Community Forest was abundant, especially in seedlings stage. G. versteegii were found in four stratas i.e., trees, poles, saplings and seedlings with densities of 6, 4, 15 and 23 plants ha-1, respectively. Seedlings of G. versteegii were abundant while larger plants were rare. Moreover, G. versteegii has scattered distribution and the highest important values (IVI) for trees, poles and saplings stratas, with IVI of 17.42, 25.75 and 44.42, respectively, while among the ground covers, G. versteegii ranked 22nd with an important value of 2.32. The abundant seedlings and the availability of adult trees as reproductive stages in the population of G. versteegii designated that population of G. versteegii in Pongkor could serve as a potential source of seed and young trees for plant enrichments in natural habitats and sustainable plantation in Manggarai District, Flores Island.